Projected inter-active display - Arcellana, Anthony A. A. (Animo Repository, 2008)
A new way to interact with sources of information using an interactive projected display is designed and developed. The ubiquitous mouse and keyboard are standard input devices to control a graphical display. However, for applications like public information say in a hall or open space, these devices suffer from mechanical abuse, short lifespan, frequent downtimes, and can be a channel of transmission of disease as several users gain access to the information service. With the advent of increased processing power and technology, there has been great interest from the academic and commercial sectors in developing new and innovative human computer interfaces that avoid any physical user contact with the information system. One particular development is the use of bare hand computer interaction. This paper discusses a camera-projector-combination solution where the Graphic User Interface (GUI) is projected on a wall by a standard LCD or DLP projector and the human interacts by "tapping" the projected images with his bare hands. A standard low resolution web-camera is used to track the user's bare hands. A tracking and triggering algorithm is proposed, developed and programmed using Microsoft Visual C++ with libraries from Intel OpenCV and Windows Platform SDK. A demo-application of a DLSU map is composed and its performance evaluated by users.